Pengaruh Budaya Organisasi, Pengembangan Karir Dan Pemeliharaan SDM Terhadap Kinerja Karyawan Studi Pada PT PG Rajawali I PG Krebet Baru - Moh. Imam Basori; Siti Asiyah; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of organizational culture, career development, and maintenance of human resources on employee performance at PT Rajawali 1 PG Krebet Baru, either simultaneously or partially. The analytical method used in this research is explanatory research and uses a quantitative approach. Collecting data using a questionnaire from a population of 51 employees and the sample used is 51 respondents. The data analysis technique used is multiple linear regression analysis.The results of the study state that the variables of organizational culture, career development, and maintenance of human resources simultaneously have a significant effect on employee performance. Organizational culture has an effect on employee performance, meaning that if the organizational culture is getting better, the performance will increase. Career development has no effect on employee performance, meaning that career development has no effect on employee performance. HR maintenance affects employee performance, meaning that if HR maintenance is getting better, performance will increase. Keywords : Organizational Culture, Career Development, Maintenance Of Human Resources, Employee Performance.